Representações sobre a maternidade e o bebê em gestantes por ovodoação - Schneider, Ivana Elia (Universidade do Vale do Rio dos Sinos, 2017)
The maternal representations during the pregnancy are fundamental for the preliminary interactions and the baby’s future psychic development. It deals with a range of expectations, fantasies, fears, perceptions about the pregnancy, herself as mother and their baby. Through the psychoanalytical referential, the objective was to investigate the maternal representations of pregnant by egg donation women about the maternity and the baby. A qualitative research of exploratory character was conducted, with a Multicase Study design. Three pregnant women with ages between 44 and 45 years participated, and a Social Demographic and Clinical Data Sheet, the IRMAG, the Interview on Assisted Reproduction and Field Notes were used as instruments. The results show that to gestate represent fertility restoration and her validity as a mother before the presence of the donor. It is concluded that the implications associated with the egg donation were presents in the representations about maternity, and that the representations about the baby are common to natural pregnancies, added with the perception of the donor’s genetics in different ways among the participants.
Keywords: Representações maternas; Gestação; Ovodoação; Maternidade; Bebê; Maternal representations; Pregnancy; Egg donation; Maternity; Baby; ACCNPQ::Ciências Humanas::Psicologia